Targeted deletion of the pancreatic β-cell oxytocin receptor and its effects on metabolic regulation and β-cell health - Mendez, Armando J.; Szeto, Angela; Boulina, Maria; Westwright, Jesica; Rahman, Hafsha; Abushamma, Sarah; Schneider, Riley; McCabe, Philip M. (Frontiers in Endocrinology, 2024)
The neuropeptide oxytocin (OXT) and its receptor (OXTR) have been shown to play an important role in glucose metabolism, and pancreatic islets express this ligand and receptor. In the current study, OXTR expression was identified in α-, β-, and δ-cells of the pancreatic islet by in situ RNA hybridization, and OXT protein expression was observed only in β-cells. In order to examine the contribution of islet OXT/OXTR in glycemic control and islet β-cell heath, we developed a β-cell specific OXTR knock-out (β-KO) mouse. In isolated islets from control mice, OXT enhanced glucose stimulated secretion of insulin, but this response was abolished in the β-KO mice. In vivo, supraphysiological doses of OXT reduced blood glucose levels in hyperglycemic Control mice and during a glucose tolerance test. Once again, this response was abolished in the β-KO mice, suggesting that β-cell OXTR may play a role in glycemic regulation. Despite these findings, β-cell deletion of OXTR had no effect on fasting glucose, fasting insulin or glucose tolerance in mice fed a low fat- or high fat-diet for 23 weeks. The low fat or high fat diets did not alter β-cell mass by immundetection or a measure of apoptosis, however, β-KO mice on a high fat diet did exhibit increased β-cell proliferation. In mice treated with the cytotoxic agent, streptozotocin, deletion of OXTR resulted in greater hyperglycemia in β-KO mice relative control mice, suggesting that β-cell OXTR may provide some cytoprotection. In conclusion, the present study provides mixed support for a role of the β-cell OXTR in glycemic regulation. On one hand, in vitro experiments and in vivo pharmacologic experiments provided evidence that under hyperglycemia, OXTR activation can potentiate insulin secretion and glucose suppression. On the other hand, β-KO followed by chronic dietary manipulation had no effect on whole body glucose regulation in vivo. In terms of β-cell health, our data suggests a role of the OXTR in β-cell proliferation and cytoprotection following metabolic or cytotoxic challenge.